The first archaeometric characterization of the Late Roman period bricks in the Dniester river basin in comparison with Early Medieval material - Ільків, Микола; Ilkiv, Mykola; Korokhina, Anastasiia; Belskyi, Volodymyr; Petrauskas, Oleg; Avramenko, Maryana; Khamaiko, Natalia; Lytvynenko, Yurii (Cuadernos de Prehistoria y Arqueología de la Universidad de Granada, 2022)
The paper presents the results on archaeometric characterization of a test sample of building materials from the settlements of the Late Roman period Komariv and Buzovytsia-1 in the middle course of the Dniester river. The parameters of raw material and technology of bricks from the two sites are compared and the first reconstruction of features of operational chains are offered. Also, the first comparison of the Late Roman period materials with same-function artifacts of the Middle Ages (Old Rus’ Culture) has been made. The development of petrographic and geochemical classification of archaeological building ceramics from the sites of the Central and South-West Ukraine was started.
Keywords: Late Roman Time, Cherniakhiv-Syntana de Muresh Culture, Middle Ages, Old Rus’, Bricks, Building Ceramics, Eastern Europe, Archaeometry